2015
DOI: 10.1590/0100-69912015001007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the different degrees of risk of gastrointestinal stromal tumor

Abstract: ABSTRACT ABSTRACT ABSTRACTObjective Objective Objective Objective Objective: To evaluate the applicability of the main categories of risk and morphological factors in the prognosis of gastrointestinal stromal tumors. MethodsMethods Methods Methods Methods: we retrospectively studied fifty-four cases of GIST, assessing the main prognostic factors of this neoplasis: risk levels, topography, size, mitotic index, necrosis, histological subtype and immunophenotype. We also verified their association and the reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
(59 reference statements)
1
6
0
Order By: Relevance
“…Even if necrosis and its related parameters were not significant indicators for ruptured GISTs according to previous studies (26), they were demonstrated to be significant predictors in high-risk stratification GISTs (24,33,39). Previous studies have also shown that necrosis is one of the pathological predictors of malignant behavior of GISTs and is more important for evaluating the prognosis of GISTs (17,36,(40)(41)(42). It is considered that necrosis is directly related to the severe proliferation of tumor portion; that is, necrosis will occur in the most invasive and aggressive area (42).…”
Section: Discussionmentioning
confidence: 94%
“…Even if necrosis and its related parameters were not significant indicators for ruptured GISTs according to previous studies (26), they were demonstrated to be significant predictors in high-risk stratification GISTs (24,33,39). Previous studies have also shown that necrosis is one of the pathological predictors of malignant behavior of GISTs and is more important for evaluating the prognosis of GISTs (17,36,(40)(41)(42). It is considered that necrosis is directly related to the severe proliferation of tumor portion; that is, necrosis will occur in the most invasive and aggressive area (42).…”
Section: Discussionmentioning
confidence: 94%
“…It was here applied because less energy is transduced to tissue compared to other devices, and do not pass electricity through the body 5,9 . Another benefit is reduction in analgesics administration in the postoperative period [10][11][12][13][14][15] .…”
Section: ■ Discussionmentioning
confidence: 99%
“…Among prognostic criteria, mitosis index is the most related to recurrence 2 , 22 . In these authors experience, patient with higher number of mitosis per 50 HPF analysis suffered early disease recurrence.…”
Section: Discussionmentioning
confidence: 99%